Physical development and general physical performance of children at the age of 5 – 10 years - Willwéber, Tomas; Čillík, Ivan (Journal of Education, Health and Sport, 2017)
The aim of this study is to find out the level of general physical performance of children in younger school age depending on the age of individuals. We present the results of body development and general physical performance of children in younger school age in this contribution. Monitored sample consisted of 80 probands at the age of 5 – 10 years: I. group 5 – 6 years (39 probands), II. group 7 – 8 years (29 probands), III. group 9 – 10 years (12 probands). We used standing long jump, knee throw over a head, 4 x 10 m shuttle run, endurance shuttle run to find out general physical performance. We did not recorded statistically significant difference (p > 0.05) in intersexual comparison in neither age group. We recorded statistically significant differences (p < 0.05) between age groups: in body height, in body weight, standing long jump, knee throw over a head, in 4 x 10 m shuttle run and in endurance shuttle run. We did not recorded any statistically significant dependence in BMI between age groups. The partial output is part of the: VEGA 1/0571/16.